Osteoimmunopathology Evidence-Based Perspectives from Molecular Biology to Systems Biology - Chiappelli, Francesco (Springer New York : Imprint: Springer, 2011)
Osteoimmunology pertains to the study of the relationship between the bones, particularly the bone marrow, and the immune system.   This monograph pursues the best available evidence, by means of research synthesis, for the characterization of the physiological relevance and pathological implications of the inter-connectedness between the skeletal and the immune system.  Research will be discussed that highlights the associated role of the circulatory, nervous and endocrine systems, as well as proteomic and genomic pathways and signatures. Emphasis is given that domain of medicine that relates to the oral cavity, its diseases and their systemic sequelae. This monograph arises from observations that have suggested that the skeletal system and the immune system are intimately intertwined. Chronic inflammatory reactions subsequent to an excessive immune reaction can damage the bones, as in rheumatoid arthritis (RA), osteoporosis, patients seropositive for the human immunodeficiency virus (HIV)-1 and with signs and sympotoms of the acquired immune deficiency syndrome (AIDS), and bone cancer. Bones - in particular the bone marrow - are one of the primary locations in which cells of the immune system mature. In brief, this monograph begins to answer a range of  questions, such as, what is osteoimmunology all about?, does the immune system and its components affect bone development?, how do stress hormones impact upon the pathophysiology of bone-immune interactions?, can the scientific process of research synthesis, obtain the best available evidence for treatment of diseases involving the bone-immune entity (i.e., osteoimmunopathologies) means of evidence-based clinical decision-making directed at the treatment of osteoimmune pathologies?